Real earnings management, liquidity risk and REITs SEO dynamics - DENG, Xiaoying (Institutional Knowledge at Singapore Management University, 2018)
We analyze how REITs managers use real earnings management to address issues of liquidity risk and increased cost of capital they face during seasoned equity offerings. We show that REITs managers engage in real earnings management instead of accrual earnings management to attract more uninformed trading in order to provide the liquidity service at a lower cost during seasoned equity offerings. We find REITs with higher liquidity risk are more likely to manipulate earnings prior to equity offerings and uninformed trading is higher following real earnings management. Firms set the offer price at a smaller discount after engaging in real earnings management and stock returns decline in the long run. The findings are consistent with real option and liquidity risk explanations for equity offerings.